2018
DOI: 10.3390/ma11030363
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Effect of Hierarchically Structured Ag-ZnO Hybrid on the Surface Antibacterial Activity of a Propylene-Based Elastomer Blends

Abstract: In this study, a hybrid Ag-ZnO nanostructured micro-filler was synthesized by the drop technique for used in plastic and medical industry. Furthermore, new antibacterial polymer nanocomposites comprising particles of Ag-ZnO up to 5 wt % and a blend of a thermoplastic polyolefin elastomer (TPO) with polypropylene were prepared using twin screw micro-compounder. The morphology and crystalline-phase structure of the hybrid Ag-ZnO nanostructured microparticles obtained was characterized by scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 61 publications
(79 reference statements)
1
6
0
Order By: Relevance
“…Constantly endangering fungus and mold can cause products to fast decrease in product quality, stability, and product shelf life. The presented review confirmed that incorporation of natural modifiers with given antibacterial properties into conventional polyurethane and polyurethane foam formulations allows preparing of antimicrobial materials with effective alternatives to expensive and currently technologies [83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102].…”
Section: Discussionsupporting
confidence: 64%
“…Constantly endangering fungus and mold can cause products to fast decrease in product quality, stability, and product shelf life. The presented review confirmed that incorporation of natural modifiers with given antibacterial properties into conventional polyurethane and polyurethane foam formulations allows preparing of antimicrobial materials with effective alternatives to expensive and currently technologies [83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102].…”
Section: Discussionsupporting
confidence: 64%
“…Notably, there is no significant diffraction peaks observed that could be due to the lattice site substitution of ZnO or for the other elements. 45 In conclusion, the XRD results showed that the NP combination system comprises elemental Ag 2 O/Ag 0 , CuO, and SnO 2 in different combinations with ZnO, and the NP systems are crystalline in nature. These results are further matching well with the transmission electron microscopy (TEM) results (fringes are visible in Figure 1).…”
Section: ■ Introductionmentioning
confidence: 79%
“…Therefore, the obtained results prove that there are significant diffraction peaks present as the evidence for the presence of AgO 2 /Ag 0 , SnO 2 , and CuO in the final composition. Notably, there is no significant diffraction peaks observed that could be due to the lattice site substitution of ZnO or for the other elements . In conclusion, the XRD results showed that the NP combination system comprises elemental Ag 2 O/Ag 0 , CuO, and SnO 2 in different combinations with ZnO, and the NP systems are crystalline in nature.…”
Section: Resultsmentioning
confidence: 99%
“…The next step of current research is to determine and observe the antimicrobial especially antibacterial properties of synthesized products one by one. Antimicrobial activities of synthetic compounds was determined by using well diffusion method according to CLSI, 2007 [ 36 ]. Further details and procedure for antibacterial activities are given in supporting information.…”
Section: Methodsmentioning
confidence: 99%